2020
DOI: 10.3390/met10121587
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hot Deformation and Precipitates on the Recrystallization of Nb-V-Ti Free-Cutting Steel

Abstract: Nb, V, and Ti were added to free-cutting steel to improve its mechanical properties by means of precipitation strengthening and fine grain strengthening. The process parameters during the hot deformation of Nb-V-Ti free-cutting steel were studied at strain rates of 0.01–10 s−1 and temperatures of 850–1250 °C. The isothermal compression test results showed that the temperature rise at low deformation temperature and high strain rate has a great influence on the softening of the steel. The processing maps at str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the case of MnS precipitates (Figure 13), the simulation showed that these only appeared at 1100 °C, while at 1000 °C, their size was negligible, which, during cooling, may directly affect the formation of M23C6 particles, as they are affected by S content. The precipitation models [19,20] indicated that, at 1100 • C, the hot forging deformation produced dynamic recrystallization. As Figure 2 indicates, the upper zone of the steel bar suffered a larger strain difference from zero to~8% which, combined with a more pronounced quenching effect (the surface in direct contact with the quenching fluid), resulted in more pronounced differences in the hardness curve (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of MnS precipitates (Figure 13), the simulation showed that these only appeared at 1100 °C, while at 1000 °C, their size was negligible, which, during cooling, may directly affect the formation of M23C6 particles, as they are affected by S content. The precipitation models [19,20] indicated that, at 1100 • C, the hot forging deformation produced dynamic recrystallization. As Figure 2 indicates, the upper zone of the steel bar suffered a larger strain difference from zero to~8% which, combined with a more pronounced quenching effect (the surface in direct contact with the quenching fluid), resulted in more pronounced differences in the hardness curve (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…As VC forms at low PSTs, it can interact with DRX during hot working conditions. Several investigations have shown that V carbonitrides can effectively pin the grain boundaries of austenite and postpone or even inhibit DRX in microalloyed steels [23,24].
Figure 5. TTP diagram of the studied alloy developed by using JMatPro 7.
…”
Section: Resultsmentioning
confidence: 99%
“…Advanced heavy steel plates with high strength and excellent cryogenic toughness are preferred as structural materials for ship hull. Especially for non-quenched and tempered ship plate steel, it is popular due to its economic applicability with fewer processes and low energy consumption [1][2][3]. In order to obtain excellent mechanical properties, non-quenched and tempered ship plate steel is often treated with microalloying or thermo-mechanical control process (TMCP) to compensate for the strength loss caused by the lack of quenching and tempering [4][5][6].…”
Section: Introductionmentioning
confidence: 99%